Religious Literacy in the Social Media Era: Islamic Religious Education (PAI) Strategies to Combat Disinformation at Madrasah Aliyah Al Muslihun - Anton Prawito (Journal of Teacher Training and Educational Research, 2025)
This study aims to describe the implementation of the 3C model (checking sources, checking claims, and checking context) in Islamic Religious Education (PAI) learning as an effort to build students’ resilience against religious mis/disinformation on social media at Madrasah Aliyah Al Muslihuun. This study employs a descriptive qualitative design, with data collected through classroom observations, semi-structured interviews with PAI teachers and selected students, and document analysis of learning artefacts. The data were analyzed using thematic analysis following Braun and Clarke’s framework. The findings indicate that the implementation of the 3C model fosters students’ habits of examining the identity and affiliation of information sources, tracing primary and secondary references, and distinguishing between opinion and fatwa, particularly when learning activities are dialogical and supported by contextual case examples relevant to students’ daily media use. However, students’ ability to critically analyze rhetorical framing and emotional narratives remains limited, and the habituation of 3C practices varies across classes depending on the availability of explicit learning tools and structured routines. This study concludes that the 3C model can be effectively habituated in PAI learning when supported by clear verification worksheets, teacher modeling, and tabayyun-oriented reflection, with implications for strengthening teacher capacity, curating ethically safe learning materials, and implementing authentic assessments to foster sustainable digital religious literacy in Madrasah Aliyah